Community Strategy for Managing Tropical Forest Resources in The Areaof Cagar Alam Pulau Sempu (Nature Reserve of Sempu Island) - Lely Mardiyanti; Rifalatul Isnaini; Sueb Sueb (UPT Penerbitan Universitas Jember, 2016)
Management of Cagar Alam Pulau Sempu (The Nature Reserve of Sempu Island) as ecotourism can increase community life in surrounding it. The objects of this study were to 1) knowing community’s knowledge about management at the Nature Reserves of Sempu Island as ecotourism, 2) knowing community’s participation to supporting management at the Nature Reserves of Sempu Island as ecotourism, and 3) knowing correlation between knowledge and participation in supporting the management of Sempu Island as ecotourism. Data collections were interviews and questionnaires with Guttman Scale which made by researchers and had been tested its validity and reliability. All questions in questionnaire is valid and 100% reliable. Samples for this research were 30 local people at Tambakrejo village. Technique of selecting that samples was accidental sampling. Most of respondents are male in 21─40 years old and graduating from junior or senior high school which are indegineous and andong people. Based on normality and homogenity test, data is homogeneous. It is not distributed normally so hypothesis test using non-parametric correlation of Spearman. Significant value 0.000 < 0.05 so H0 is rejected. Correlation between knowledge and participation is in strong category with Spearman’s correlation coefficient (R) = 0.732. The conclutions of this study are the highest score of community’s knowledge is 97% and its lowest score is 6,7%, the highest score of community’s participation is 97% and its lowest score is 20%, there is correlation between community’s knowledge and community’s participation in the management at Nature Reserve of Sempu Island as ecotourism.